Corporate Environmental Citizenship Variation in Developing Countries: An Institutional Framework - Özen, Şükrü; Küskü, Fatma (Springer Science and Business Media LLC, 2008)
This study focuses on why some companies in developing countries go beyond environmental regulations when implementing their corporate environmental social responsibilities or citizenship behavior. Drawing mainly upon the new institutional theory, this study develops a conceptual framework to explain three institutional factors: companies’ market orientations, industrial characteristics, and corporate identities. Accordingly, we suggest that companies from developing countries that are oriented to markets in developed countries, operate in highly concentrated industries, and have missionary identities adopt corporate environmental citizenship behavior by going beyond environmental regulations. The study also discusses the theoretical, policy, and managerial implications of the conceptual framework.